Mapping habitat suitability and connectivity for the Sunda clouded leopard (Neofelis diardi) in Batutegi Protected Forest, Lampung, Indonesia - HAFIZ NUR MALIK; DEDE AULIA RAHMAN; YUDI SETIAWAN; ROBITHOTUL HUDA (Society for Indonesian Biodiversity, 2024)
Abstract. Malik HN, Rahman DA, Setiawan Y, Huda R. 2024. Mapping habitat suitability and connectivity for the Sunda clouded leopard (Neofelis diardi) in Batutegi Protected Forest, Lampung, Indonesia. Biodiversitas 25: 2249-2256. One of the rarest and least understood species of carnivore, the Sunda clouded leopard (Neofelis diardi Cuvier, 1823), is facing considerable threats from continued habitat loss and fragmentation. The Batutegi Protected Forest, Lampung, Indonesia, which was recently identified as an existing but isolated habitat of this vulnerable felid, is also experiencing fragmentation and encroachment. These combined threats have led to a reduction in the availability of suitable habitats for this isolated population and created barriers restricting its movement between forested areas. Understanding the factors that influence habitat selection and developing ecological corridors to improve its connectivity is critical to the conservation of the Sunda clouded leopard in Batutegi Protected Forest. We examined camera trap data and used maximum entropy modeling to construct a habitat suitability map, which was used to develop the resistance surface. We then performed habitat connectivity analysis using least-cost modeling. Our results indicated that there was a moderate potential in some areas of the study region to support the occurrence of Sunda clouded leopard, whose presence was mainly driven by the presence of forested landscapes and higher elevations. The predicted connectivity network revealed that the most suitable corridor could facilitate the movement of Sunda clouded leopards between forested areas by avoiding the monoculture plantations and mainly crossing through a matrix of forested patches and mixed plantation areas. This study contributes important insights to assisting in the prioritization of habitat conservation for the protection of Sunda clouded leopard and overall forest biodiversity due to its capacity as an umbrella species.